The Role of Public Diplomacy the Indonesia Oscar Selection Committee: A Case Study of Indonesia's Film Submission to the Oscars - Andriano, Stefanus (Jurnal Pewarta Indonesia, 2025)
This paper aims to explore the question: "How does The Indonesia Oscar Selection Committee (IOSC) contribute to public diplomacy?" Public diplomacy is a widely recognized tool in international relations, used to influence foreign audiences. It involves diplomatic actions taken by both government and non-government actors to advance national interests. Numerous mediums can be employed in public diplomacy, including literature, television, brands, festivals, consumer products, and films. In practice, much of the information about a country often comes from non-state actors, such as Indonesia’s film industry. Ideal public diplomacy requires a collaborative effort between governmental and non-governmental entities (Leonard, 2002). This study examines how the film industry, through the activities of the Indonesia Oscar Selection Committee (IOSC), serves as an instrument of public diplomacy. Using Mark Leonard’s public diplomacy theory, the study employs a qualitative descriptive approach, gathering data through interviews and literature review from both primary and secondary sources. The research offers insights into how IOSC’s activities align with Leonard’s public diplomacy framework, identifying potential gaps between theoretical concepts and real-world practices. Ultimately, the study argues that IOSC has significant potential to promote effective public diplomacy, and it underscores the importance of enhancing collaboration between IOSC and the Indonesian government to optimize IOSC’s role in advancing Indonesia’s international image through cinema.